2007
DOI: 10.1007/s10856-007-3278-0
|View full text |Cite
|
Sign up to set email alerts
|

Stealth dendrimers for drug delivery: correlation between PEGylation, cytocompatibility, and drug payload

Abstract: It is advantageous to utilize low generation polyamidoamine (PAMAM) dendrimers for drug delivery because low generations (generation 4.0 or below) have more biologically favorable properties as compared to high generations. Nevertheless, modification of low generation dendrimers with PEG to create stealth dendrimers is still necessary to avoid potential side effects by long term accumulation. However, low generation dendrimers have much fewer surface sites for drug loading as compared to higher generations. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 17 publications
3
61
0
Order By: Relevance
“…However, MSC nanoparticle loading was not expected for cells incubated with PEGylated nanoparticles because of the well documented evidence for polyethylene glycol as a s tealthing agent. 23,24 Due to the fact that the nanoparticle formulations used in this study did not incorporate targeting agents (eg, targeting antibodies), nanoparticle uptake by cells was passive, and thus MSCs were unable to detect and passively uptake PEGylated nanoparticles.…”
Section: Msc Nanoparticle Loadingmentioning
confidence: 99%
“…However, MSC nanoparticle loading was not expected for cells incubated with PEGylated nanoparticles because of the well documented evidence for polyethylene glycol as a s tealthing agent. 23,24 Due to the fact that the nanoparticle formulations used in this study did not incorporate targeting agents (eg, targeting antibodies), nanoparticle uptake by cells was passive, and thus MSCs were unable to detect and passively uptake PEGylated nanoparticles.…”
Section: Msc Nanoparticle Loadingmentioning
confidence: 99%
“…26) Yang et al have also showed that the cytotoxicity of PAMAM dendrimers was significantly reduced through PEGylation. 27) Both 3PEGs-G3.0 (PEGylation degree 9%) and 8PEGs-G3.0 (PEGylation degree 25%) gained significantly improved cytocompatibility as compared to unmodified dendrimers. 27) This can be explained by reduction of the overall positive charge when transforming the basic primary surface amino groups to noncharged amides as well as encapsulating the dendrimer cationic interior tertiary amines.…”
Section: Discussionmentioning
confidence: 92%
“…27) Both 3PEGs-G3.0 (PEGylation degree 9%) and 8PEGs-G3.0 (PEGylation degree 25%) gained significantly improved cytocompatibility as compared to unmodified dendrimers. 27) This can be explained by reduction of the overall positive charge when transforming the basic primary surface amino groups to noncharged amides as well as encapsulating the dendrimer cationic interior tertiary amines. 26) Our experiments made with annexin V-FITC and detection of apoptosis by a fluorescent microscopy assay revealed that G2 and G3 PAMAM-NH 2 dendrimers inhibited the proliferation of MCF-7 and MDA MB-231 malignant cells by increasing the number of apoptotic and necrotic cells.…”
Section: Discussionmentioning
confidence: 92%
“…22 Moreover, PEGylated biomacromolecules are approved by the FDA and attachment of PEG to dendrimers provides several other pharmacological advantages, such as increased blood circulation time, lower/nonimmunogenicity, and improved bio-distribution. [23][24][25][26] Furthermore, the inclusion of PEG chains in the backbone of dendrimers also enhances water solubility, which in turn improves bioavailability and pharmacokinetic profiles. During the past decade, significant progress has been made in the field of dendrimer syntheses, indicating that many of the drawbacks, such as high cost, multi-step synthesis, low reproducibility and complex purification procedures, can be partly resolved.…”
Section: Introductionmentioning
confidence: 99%